Challenges and Strategies for Parents of Hearing-Impaired Students in Cebu - Tanlangit, Denivie A.; Abellana, Juvy G.; Espina, Raymond C.; Pantaleon, Anabelle T.; Mangubat, Randy C.; Calasang, Veronica O. (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study aims to examine the extent of parental involvement among families of deaf students and its effects on their academic performance. The study was conducted at two special schools catering Hearing Impairment (HI) in Cebu namely Tabunoc Central School SPED Center in Talisay City and First High School for the Hearing Impaired (FHSHI) in Cebu City. Data were collected and analyzed through structured survey questionnaire. By using the descriptive correlational approach, the research aims to describe the correlation between the parental involvement and problems encounter in rearing their children who are deaf. The results indicated that the level of issues faced by the respondents, particularly regarding financial challenges, was a significant concern, whereas other issues were less common. In examining the impact of family dynamics on students' academic performance, particularly regarding parental engagement, the correlation coefficient revealed a strong positive relationship. This finding indicates that increased parental involvement is linked to improved academic results. Consequently, the null hypothesis was dismissed. This research strongly advocates for the establishment of support groups and local government initiatives aimed at assisting parents of children with hearing impairments, addressing various challenges and concerns associated with raising these children. Consequently, this approach can enhance the overall well-being of parents, enabling them to provide the best support for their children to thrive in life.